1979
DOI: 10.3758/bf03335024
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenic and paranoid thinking in conceptual performance

Abstract: Thirty-two hospitalized patients diagnosed as schizophrenic were assigned in equal numbers to four groups on the basis of their scores on the Whitaker Index of Schizophrenic Thinking (WIST) and the paranoid (Pal scale of the MMPI. Subjects attempted to solve two conceptformation problems in which they were to identify relevant stimulus attributes, under two levels of demand on their memories for previous stimuli. Only in conjunction with a low score on the Pa scale did the schizophrenic index predict a concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…Of the 40 schizophrenic subjects, 17 were diagnosed as paranoid and 14 of these obtained the lowest Indices on the WIST, compared to other schizophrenic patients. This finding supports the Simpson et al (1979) study, which concluded that paranoid schizophrenics are better preserved cognitively than nonparanoid patients who are equally schizophrenic.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 40 schizophrenic subjects, 17 were diagnosed as paranoid and 14 of these obtained the lowest Indices on the WIST, compared to other schizophrenic patients. This finding supports the Simpson et al (1979) study, which concluded that paranoid schizophrenics are better preserved cognitively than nonparanoid patients who are equally schizophrenic.…”
Section: Discussionsupporting
confidence: 90%
“…The finding that schizophrenic thinking does not appear to be related to neuroleptic dosage as measured by the WIST, MMS, and SCS supports numerous previous findings (Pishkin et al, 1977;Neborsky et al, 1981;Simpson et al, 1979;Tune et al, 1980). Furthermore, it extends these findings because the present study attempted to alleviate several of the design limitations in the earlier studies reviewed.…”
Section: Discussionsupporting
confidence: 86%
“…Pishkin, Lovallo, Lenk, and Bourne (1977) reported that drug dosage and cognitive performance were not related when schizophrenics were grouped according to the WIST Index or the total score on the WIST. Simpson, Bourne, Justesen, and Rhodes (1979) reported similar findings in a study that focused on conceptual performance. The results of the study indicated that WIST total score or Index correlated --06 with drug dosage.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Pishkin and Bourne (1981) caution that their findings apply to chronic undifferentiated schizophrenics and may not apply to schizophrenics in gen eral. Paranoid schizophrenics performed better on rule based problems than did non-paranoid schizophrenics in a study by Simpson et al (1979). The literature in this area is generally in agreement that schizophrenics often perform poorly on cognitive tasks, however, it is difficult to assess the significance of cognitive defects due to the heterogenous nature of the disorder, confounding effects of treatment, and differences in performance among types of schizophrenics.…”
Section: Application Of Findingsmentioning
confidence: 99%